Analisis Kompensasi Disiplin Dan Motivasi Terhadap Kinerja Karyawan Perusahaan Kargo Di Kota Batam - Wasiman Wasiman (Prosiding, 2022)
This study aims to see the effect of compensation, discipline, and motivation on the performance of cargo company employees in Batam City. This study uses a questionnaire distributed to employees of cargo companies in Batam City with a questionnaire of 120 respondents. This research uses individual level analysis. The object of research is the employee of the Batam City cargo company. This study uses multiple linear regression test which includes validity, reliability, normality, and r-square tests. The results showed that the results of the validity test showed that all indicators showed validity results that could lead to the next stage, and also the reliability results that all data collected were reliable. The coefficient of determination (R2) is 0.850, meaning that this variable can be explained by the competence, discipline and motivation variables of 85%, while 15% is influenced by other factors outside of the measured variables